Respeito ao dever e dever de respeitar: o sumo bem provisório e a religião em Kant - Pereira, Ederson da Rosa (2021)
This study deals with morality and religion in Immanuel Kant (1724-1804). The provisional Highest Good concept is presented, as an experience of sensify the ideal of the final Highest Good. Without removing its due importance and place in the Kantian moral system, it presents itself as an experience that pragmatically brings happiness and morality closer together. This approximation is possible through the principle of respect, which is the sentimental conscience or conscious feeling of the moral law. As a conscience, it legitimizes the law as a formal principle for moral action in determining the will. As a feeling, he acts on sensitivity, pacifying it and directing it to obedience. With his will determined, the moral agent is not subjected to the dictates of his volitional nature and is able to obey the rational duties that are also his ends. As he conforms to the law more than his passions, due to autocracy, he is able to feel satisfaction in his duty. In this way, they impose themselves, purposes which are, at the same time, their duties. These purposes correspond to the maximum ideal thought, imagined and sought as a model of self-perfection and the promotion of others. To act pragmatically in terms of these two duties is to carry out the provisional Highest Good in empirical experience. This is the model of the moral-religious man, who follows a system of purposes that are duties, becoming moral and happy at the same time. The provisional Highest Good is a “copy” or a living representation of the final Highest Good – happiness and morality in fullness and equal proportion. The moral and happy man is a religious man. And it is in this way that, in Kant's view, human Religion, universal and valid for all human beings, is made visible in society, the environment in which Religion is exercised. The moral and happy man, fulfilling his duties and promoting the happiness of others, is Kant's contribution not only to philosophy but to the Science of Religion (SR) and other human sciences